STUDY OF PHENOLIC COMPOUNDS IN OLIVE OIL WHICH EXTRACTED FROM SOME VARIEITIES AND DURING STORAGE - S. Al-Obady (Mesopotamia Journal of Agriculture)
Three type of olive oil (Iraqi, Syrian and Spanish)had been taken from the local makets, the first aim of this study is to determination of phenolic compound s quantity and chlorophel A&B which transfer from olive to oil after storage in darknees for three months at 7,15 &30◦C .The second aim of this study was to know the estimating and analyzing of some factors affecting he quality of oil (refractive index, relative density, free fatty acid, peroxide value and saponification value). Organoleptic evaluation was done till the end of the storage period , we used linear regress analysis to try to find relationship between phenolic compound content in olive oil and peroxide value and chlorophel A&B content . The results showed that phenolic compounds and chlorophel content decreased during storage period for all type of olive oil and all the temperature storage, Thus some of the oil constants was increased for all type of olive oil and all a degree of storage. The highest increasing occurred at 30°C , linear regress analysis and %R2 showed that they found relationship between the two properties, organoleptic evolution showed that the best type of sample at the end of storage was Syrian, Iraqi and Spanish .